Pengaruh Model Kepemimpinan Kiai Di Pondok Pesantren Dan Sistem Ujrah Terhadap Produktivitas Kinerja Guru Dan Karyawan Di SMK Miftahul Waritsin - Supandi, Ach. Faqih; Nadlif, Muhammad; Hannah, Miftakhul (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This study aims to analyze the influence of the Kiai Leadership Model in Islamic Boarding Schools and the Ujrah System on the Work Productivity of Teachers and Employees at Miftahul Waritsin Vocational School. This study uses quantitative research with data collection techniques through observation, questionnaires and documentation. Data collection uses statistical data analysis research instruments with the aim of testing the hypotheses that have been set. The population in this study were all teachers and employees of SMK Miftahul Waritsin. The sampling technique used is probability sampling, which is a sampling technique that provides equal opportunities for all members of the population to be selected as samples. Then this sampling technique was combined with the cluster random sampling technique, which is a technique for selecting a sample from small unit groups with a total sample taken of 21 teachers and employees at Miftahul Waritsin Vocational School. In processing the data, researchers used the SPSS 28 program. Researchers used multiple linear regression analysis. Based on the results of the research and the results of data analysis and discussion of the results of the data it was concluded that the Kiai Leadership Model (X1) obtained tcount -951 < ttable 1.986 and a significance value (sig) 0.001 <0.05 with this indicating that the Leadership Model variable has no significant effect on Productivity Performance teachers and employees. While the Ujrah System (X2) obtained tcount 429 > ttable 1.986 and a significance value (sig) 0.001 <0.05 which indicates that the Ujrah System variable has a significant effect on the Productivity and Performance of teachers and employees. Keywords: Leadership Model, Ujrah and Productivity.